Fully distributed hierarchical control strategy for multi‐inverter‐based AC microgrids. Issue 13 (16th September 2020) - Pullaguram, Deepak; Rana, Rubi; Mishra, Sukumar; Senroy, Nilanjan
Abstract : A fully distributed hierarchical control strategy for multiple inverters‐based AC microgrid is proposed. The developed controller provides real‐time economic dispatch along with the network frequency and average voltage restoration. The controllers cooperate with neighbours using sparse communication network and perform local computations to achieve the assigned objectives. The economic dispatch control unit is embedded with the frequency restoration at the secondary level controller to change the active power supply from the inverter. The voltage controller along with reactive power controller ensures the proportional reactive power sharing as well as network average voltage regulation. The average voltage regulation aids the individual inverter to provide required reactive power demand, with a small, comprise at the terminal output voltages from the nominal values. The convergence of the proposed controller is proved using the Lyapunov stability criteria. The maximum allowable communication delay that obligate stable microgrid operation is derived. The simulation results verify the efficacy of the proposed controller. Experimental validation is also presented, and the controller ability to ride through communication failure and load perturbation condition is demonstrated.